Penentuan Lokasi Gudang Baru Menggunakan TOPSIS dan Pembobotan PIPRECIA - Wahyudi, Agung Deni (PT. Tech Cart Press, 2024)
Determining the location of a new warehouse is a strategic decision that can affect the operational efficiency and costs of the company. Some problems that may arise in determining the location of the new warehouse are the area of the new warehouse, distance to the factory, distance from the main warehouse, average distance to the distributor. New warehouse siting recommendations can be generated by integrating the TOPSIS and PIPRECIA methods. TOPSIS provides a relative evaluation of each site based on predetermined criteria, while PIPRECIA helps address the weighted aspects of the criteria used in determining the location of new warehouses. The results of alternative ranking provide recommendations in the selection of new warehouse locations, namely the first rank with a value of 0.8223 with the alternative name of Region 4, the second rank with a value of 0.6163 with the alternative name of Region 3, the third rank with a value of 0.5049 with the alternative name of Region 5.